Supplementation of microencapsulated sodium butyrate on the performance, haemato-biochemical profile and intestinal microbiota composition of broiler chickens challenged with Eimeria spp. - Barbosa, Bárbara Fernanda da Silva [UNESP]; de Lima, Gabrieli Andressa [UNESP]; Ventura, Gabriela [UNESP]; Trevizan, Bruna Abrahão [UNESP]; Castillo, Elis Omar Figueroa [UNESP]; Bortoloto, Jéssica Tuane [UNESP]; Polycarpo, Gustavo do Valle [UNESP]; Biller, Jaqueline Dalbello [UNESP]; Madeira, Alda Maria Backx Noronha; Cruz-Polycarpo, Valquíria Cação [UNESP] (Canadian Science Publishing, 2024)
The aim of this study was to evaluate the effect of microencapsulated sodium butyrate (MSB) in substitution to antibiotics on performance, haematology, intestinal lesion scores, and oocyst count in the excreta of broilers challenged with Eimeria spp. A total of 1050 male Ross chicks were used, distributed in completely randomized design, with six treatments: unchallenged control diet (UC); challenged control diet (CCD); challenged and supplemented (CS) with 1000 mg/kg of MSB; CS with 1500 mg/kg of MSB; CS with 2000 mg/kg of MSB; and CS with avilamycin, with five repetitions. At 16 days of age (d.o.), the birds were inoculated orally with Eimeria spp. oocysts. Higher average weightgain (AWG) and average feed intake (AFI) were observed in the UC, and at the 42 d.o., better feed conversion ratio (FCR) and productive efficiency factor (PEF). The group that received the additives showed higher relative abundance of the phylum Bacteroidetes, as well as that of the unchallenged birds; however, the CCD had higher relative abundance of the phylum Firmicutes. It is concluded that MSB can be used as an alternative to antibiotics, assisting in the recovery of performance and gut microbiota biodiversity.
Keywords: blood profile; butyric acid; coccidiosis; gut health; poultry